A review on the methane emission detection during offshore natural gas hydrate production - Liu, Shuangxing; Xue, Ming; Cui, Xiangyu; Peng, Wenzheng (Frontiers in Energy Research, 2023)
Due to the high energy density, large potential reserves and only release CO2 and water after combustion, natural gas hydrate (NGH) is considered as the most likely new clean energy source to replace traditional fossil energy (crude oil, natural gas, etc.). However, unlike the exploitation of traditional fossil energy, the essence of natural gas hydrate exploitation is to induce the production of methane by artificially decompose the natural gas hydrate and to simultaneously collect the generated methane. Because of the uncontrollable decomposition, the methane percolation and the gas collection efficiency, methane emission is inevitably occurred during natural gas hydrate exploitation, which could significantly affect the environmental friendliness of natural gas hydrate. In this review, the methane emission detection was divided into three interfaces: Seafloor and sediment, seawater, atmosphere. Meanwhile, according the summary and analysis of existing methane emission detection technologies and devices, it was concluded that the existing detection technologies can identify and quantify the methane emission and amount in the three interfaces, although the accuracy is different. For natural gas hydrate exploitation, quantifying the environmental impact of methane emission and predicting the diffusion path of methane, especially the methane diffusion in strata and seawater, should be the focus of subsequent research.